The impact of befriending and peer support on family carers of people living with dementia: A mixed methods study. (May 2018) - Smith, Raymond; Drennan, Vari; Mackenzie, Ann; Greenwood, Nan
Highlights: Whilst little measurable impact on emotional health and loneliness from the outcome scales was found, carers described talking to the volunteers and sharing their feelings as valuable. This led them to feel emotionally supported, enabled them to cope with difficult situations and to continue caring. Quantitative results showed statistically significant improvements in perceived social support from a significant other. This was corroborated by the qualitative findings, with carers reporting they were no longer socially isolated and felt supported by the volunteers. The development of successful befriending and peer support relationships was often facilitated by the similarity of the carers' and volunteers' characteristics and the shared experience of caring. Abstract: Background: Volunteer led befriending and peer support is provided to a wide range of people with varying needs. Despite large numbers of such schemes for carers of people with dementia, there is little evidence for any benefits they may offer. The aim of this research was to investigate the impact of befriending and peer support on carers of people with dementia and to explore their experiences of receiving the interventions using a mixed methods approach. Methods: Nineteen carers of people with dementia were recruited from befriending and peer support services. Carers completed the Hospital Anxiety and Depression Scale (HADS), the Multidimensional Scale of Perceived Social Support (MSPSS) and UCLA Loneliness Scale at baseline, three months and six months. Of the 16 carers who completed the quantitative phase, eight took part in depth semi-structured interviews. Results: A statistically significant increase in perceived social support from a significant other between baseline and three months was found (Z = 2.487, p = 0.013). Qualitative findings showed befriending and peer support to be important sources of emotional and social support for carers, which was facilitated by the volunteers' experiential similarity. Conclusion: Volunteer led befriending and peer support offers carers of people with dementia emotional and social support which enables them to cope better with challenges and continue caring. This has important implications for potentially reducing breakdowns in carer mental and physical health. Future research should explore whether these finding are replicable in other locations and in more diverse populations.